The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/smi.3026
|View full text |Cite
|
Sign up to set email alerts
|

Work–family conflict and dangerous driving behaviours: The mediating role of affect

Abstract: This study examined the under-studied relationship between work-family conflict and dangerous driving behaviours in a sample of employees, and job-related affect as a mediator of this relationship. The sample consisted of 476 Malaysian drivers (44.7% male; 55.3% female) aged 19-60 years. The participants completed scales measuring bidirectional work family conflict (work interference with family[ WIF]; family interference with work [FIW]), job-related negative affect, dangerous driving behaviours and socio-dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 84 publications
(145 reference statements)
0
10
0
Order By: Relevance
“…This finding is corroborated by studies that show the need to be powerful, dominant, respected, and reckless driving are avenues to express masculinity (Begg & Langley, 2001;Harré et al, 2000;Janssens et al, 2007;. There is a correlation between masculinity and driving styles, where men are more likely to engage in aggressive driving and speeding (Guggenheim et al, 2020;Maxwell et al, 2020;Shukri et al, 2021). Violence, intimidation, and domineering attitudes were displayed among illegal racers which was a sign of high masculine identity.…”
Section: Discussionmentioning
confidence: 80%
“…This finding is corroborated by studies that show the need to be powerful, dominant, respected, and reckless driving are avenues to express masculinity (Begg & Langley, 2001;Harré et al, 2000;Janssens et al, 2007;. There is a correlation between masculinity and driving styles, where men are more likely to engage in aggressive driving and speeding (Guggenheim et al, 2020;Maxwell et al, 2020;Shukri et al, 2021). Violence, intimidation, and domineering attitudes were displayed among illegal racers which was a sign of high masculine identity.…”
Section: Discussionmentioning
confidence: 80%
“… 7 , 26 In the regression model it was found that several psychosocial work factors such as supervisor support, decision autonomy, skill discretion, psychological demands, work–family conflicts, and PSC predicted the occurrence of RTCs, as also reported in previous studies. 13 , 16 18 , 25 For instance, job demands, job resources, and work–family conflicts are associated with RTCs among rapid bus transit operators, intercity bus drivers, and other professional drivers in Colombia 6 , 15 , 17 , 25 and Malaysia. 18 …”
Section: Discussionmentioning
confidence: 99%
“… 13 , 16 18 , 25 For instance, job demands, job resources, and work–family conflicts are associated with RTCs among rapid bus transit operators, intercity bus drivers, and other professional drivers in Colombia 6 , 15 , 17 , 25 and Malaysia. 18 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations